Accessing factors influencing muslim consumer preference towards islamic home financing: an exploratory study evidence / Nurul Fadzliana Mohd Fauze - Mohd Fauze, Nurul Fadzliana (2018)
Home financing can be describe as a compulsory need for each person in this new era to purchase a house. As a Muslim, choosing a home financing that follow a Sharia laws can be assume as a good practise of life nowadays. It is because, home financing loan that follow Sharia laws mechanism now are highly offers by banking sectors. However, there is lack of study about the likelihood preferences in Islamic home financing scheme among Muslim community. Therefore, the researcher tends to explore the factor that can affect the preferences level of Muslim community in choosing Islamic home financing. The analysis of validity and reliability confirm that all indicator that were used to measure the variables in this study is valid and reliable. By using the multiple linear regression analysis, the result indicate that all the selective independent variable were having a positive significant influence towards Muslim preferences of choosing the Islamic home financing. Hence, the analysis suggest that, the responsible parties should more focus on these factor in increasing the possibility of Muslim community to choose Islamic home financing mechanism.